Surface treated copper foil and method for producing the same

By forming a roughened layer on the electrolytic copper foil and covering the nickel layer with anti-rust layer, the problem of lowering the bonding strength of the printed circuit board in the corrosion environment is solved, and a high reliability and long-life printed circuit board is achieved.

CN114929944BActive Publication Date: 2025-02-25MOUSSING WAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080087741.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-11-10
Publication Date
2025-02-25
Estimated Expiration
2040-11-10

AI Technical Summary

Technical Problem

In IoT-based information and communication equipment, the electrolytic copper foil of the printed circuit board is susceptible to corrosive gases or particles, resulting in a decrease in bonding strength, which in turn affects the reliability and life of the equipment.

Method used

By forming a roughening layer on at least one side of the electrolytic copper foil and covering the rust-proof layer with a nickel layer on the roughening layer, ensuring that the non-contact roughness and surface roughness of the rust-proof layer are within a specific range to improve the rust-proof layer and the rust-proof layer. The bonding strength of the resin substrate and corrosion resistance.

Benefits of technology

It is achieved to maintain high bonding strength when exposed to corrosive gases or particles, ensuring the reliability and long life of printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003697658370000111
    Figure BDA0003697658370000111
Patent Text Reader

Abstract

In order to avoid failure of electronic components caused by corrosion, a surface-treated copper foil and a method for manufacturing the same are provided, wherein the surface-treated copper foil can maintain high bonding strength between the electrolytic copper foil and the resin substrate even when exposed to corrosive gas or particles. The surface-treated copper foil of the present invention comprises: an electrolytic copper foil, a roughening layer covering at least one side of the electrolytic copper foil, and an antirust layer further covering the roughening layer, wherein the antirust layer is at least one surface of the surface-treated copper foil and has at least a nickel layer, and the thickness of the nickel layer is 0.8 to 4.4 g / m2 in terms of the mass of nickel per unit area. 2 The non-contact roughness Spd of the anti-rust layer is 1.4 pieces / μm 2 Up to 2.6 / μm 2 The surface roughness RzJIS of the rust-proof layer is 1.0 μm to 2.5 μm. The method for manufacturing the surface-treated copper foil forms a roughened layer having a roughness greater than the non-contact roughness Spd and the surface roughness RzJIS on one surface of the electrolytic copper foil, and then forms a rust-proof layer that satisfies the above-mentioned specified conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-treated copper foil and a method for producing the same, and more particularly to a surface-treated copper foil for use as a negative electrode collector of a secondary battery such as a lithium-ion battery or a printed wiring board and a method for producing the same. Background Art

[0002] In recent years, electrolytic copper foil has been used in various applications such as secondary batteries such as lithium-ion batteries or printed circuit boards because it is superior to piezoelectric copper foil in mass production and has relatively low manufacturing costs. In particular, in secondary batteries such as lithium-ion batteries, electrolytic copper foil is suitable for use as a material for negative electrode collectors. As a reason for this, it can be cited that the adhesion to the negative electrode active material composed of carbon, etc. is high, the manufacturing cost is low, the productivity is also high, and it is easy to thin the layer as described above. In addition, portable terminals such as smart phones have become common, and the high performance and miniaturization of electronic devices are accelerating in parallel. In addition, the popularization of wearable products and IoT is also underway, which requires further high densification of printed circuit boards. This high density is not only derived from the miniaturization of electronic components represented by semiconductors, but also from the increase in wiring density due to the miniaturization (fine pattern) of printed circuit boards.

[0003] In addition, when the electrolytic copper foil is used for the above-mentioned purpose, it is sought to improve the adhesion with the resin substrate. For example, a surface-treated copper foil is described in Reference 1, which has a surface-treated coating on at least one surface of the electrolytic copper foil, and the surface-treated coating at least includes a roughened surface formed with roughened particles. It is disclosed that the surface-treated copper foil has a standard deviation of the particle height of the roughened particles on the surface of the surface-treated coating of the surface-treated copper foil of 0.16 μm or more and 0.30 μm or less, and the average value of the ratio of the particle height of the roughened particles to the particle width (particle height / particle width) is 2.30 or more and 4.00 or less.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: Patent publication No. 2018 / 181726. Summary of the invention

[0007] Problems to be solved by the present invention

[0008] With the development of IoT, all objects such as clothes (wearable devices), cars (smart cars), and houses (smart homes) are becoming smarter in the Internet, which used to be mainly connected to IT-related devices such as personal computers and servers. In addition, a society is developing in which terminals and objects can autonomously cooperate with each other without necessarily involving people. With this, the communication system is rapidly developing in terms of high speed and large capacity, and the performance requirements for communication components are greatly increased.

[0009] Such information communication equipment uses printed wiring boards. The printed wiring board is generally manufactured by heating and pressing a substrate made of an insulator such as a resin and a copper foil as a circuit to produce a copper-clad laminate, then etching to form a circuit, and mounting electronic components.

[0010] On the other hand, in terms of convenience and comfort, the failure of electronic devices can lead to information loss, and one of the main causes of such failures is the corrosion caused by high relative humidity and corrosive gases or particles of electronic components. For example, as users spend more time using smartphones or wearable products outdoors or in cars, the chances of smartphones or wearable products being exposed to high relative humidity or corrosive gases increase, which promotes the degradation of IoT devices such as smartphones or wearable products. In addition, although the surface of copper foil can also be treated with chromate to prevent corrosion, it is desirable not to use chromium from the perspective of environmental issues.

[0011] Therefore, in order to avoid such failures caused by corrosion, an object of the present invention is to provide a surface-treated copper foil and a method for producing the same, wherein the surface-treated copper foil can maintain high bonding strength between the electrolytic copper foil and the resin substrate even when exposed to corrosive gas or particles.

[0012] Means used to solve problems

[0013] In order to achieve the above object, as one embodiment of the present invention, a surface-treated copper foil is provided, the surface-treated copper foil comprising: an electrolytic copper foil, a roughened layer covering at least one side of the electrolytic copper foil, and an antirust layer further covering the roughened layer, the antirust layer being at least one surface of the surface-treated copper foil, the antirust layer comprising at least a nickel layer, the thickness of the nickel layer being 0.8 g / m2 in terms of the mass of nickel per unit area. 2 Up to 4.4g / m 2 The non-contact roughness Spd of the anti-rust layer is 1.4 pieces / μm 2 Up to 2.6 / μm 2 , and the surface roughness RzJIS of the rust-proof layer is 1.0 μm to 2.5 μm.

[0014] The rust-proof layer may further include a chromate treatment layer and / or a silane coupling agent treatment layer as required.

[0015] Preferably, a composite metal layer of copper and at least one metal selected from molybdenum, zinc, tungsten, nickel, cobalt and iron is further provided between the electrolytic copper foil and the roughened layer.

[0016] Another embodiment of the present invention is a method for producing a surface-treated copper foil, the method comprising a roughening treatment step and a rust-proofing treatment step, wherein the roughening treatment step forms a roughening layer on at least one surface of the electrolytic copper foil, wherein the non-contact roughness Spd of the roughening layer is greater than 2.6 pieces / μm 2 , and the surface roughness RzJIS of the roughened layer is greater than 2.5 μm, and the anti-rust treatment step forms at least a nickel layer as an anti-rust layer on the roughened layer, wherein the thickness of the nickel layer is 0.8 g / m 2 Up to 4.4g / m 2 , so that the non-contact roughness Spd of the rust-proof layer is 1.4 pieces / μm 2 Up to 2.6 / μm 2 , and the surface roughness RzJIS of the rust-proof layer is 1.0 μm to 2.5 μm.

[0017] The rust-proofing process may further include chromate treatment and / or silane coupling agent treatment in addition to forming the nickel layer as required.

[0018] Preferably, the following step is also included: before the roughening treatment step, a composite metal layer is formed on the surface of the electrolytic copper foil where the roughening layer is formed, using an electroplating bath containing copper and at least one metal selected from the group consisting of molybdenum, zinc, tungsten, nickel, cobalt and iron.

[0019] Effects of the Invention

[0020] Thus, according to the present invention, a rust-proof layer having at least a nickel layer is formed on the roughened layer on at least one surface of the electrolytic copper foil, and the thickness of the nickel layer is 0.8 g / m2 in terms of the mass of nickel per unit area. 2 Up to 4.4g / m 2 , the non-contact roughness Spd of the rust-proof layer is 1.4 pieces / μm 2 Up to 2.6 / μm 2 In addition, the surface roughness RzJIS of the rust-proof layer is set to 1.0 μm to 2.5 μm. When the surface-treated copper foil is used for secondary batteries or printed circuit boards, the bonding strength with the resin substrate provided on the rust-proof layer of the surface-treated copper foil can be improved, and a high bonding strength can be maintained even when exposed to corrosive gases or particles. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the electrolytic copper foil and the method for producing the same according to the present invention will be described. However, the present invention is not limited to the embodiments described below.

[0022] [Surface treated copper foil]

[0023] The surface-treated copper foil of this embodiment comprises an electrolytic copper foil, a roughened layer covering at least one side of the electrolytic copper foil, and an antirust layer further covering the roughened layer. The antirust layer is at least one surface of the surface-treated copper foil, and the non-contact roughness Spd of the antirust layer is 1.4 pieces / μm. 2 Up to 2.6 / μm 2 , and the surface roughness RzJIS of the rust-proof layer is 1.0 to 2.5 μm.

[0024] The non-contact roughness Spd is measured according to ISO 25178. The non-contact roughness Spd represents the number of peak vertices per unit area (unit: number / μm 2 ), the larger the value, the greater the number of contact points with other objects in contact with the surface. The lower limit of the non-contact roughness Spd is preferably 1.5 / μm 2 More preferably, 1.7 pieces / μm 2 The upper limit of the non-contact roughness Spd is preferably 2.2 pieces / μm 2 Below, more preferably 2.0 pieces / μm 2 the following.

[0025] The surface roughness RzJIS is measured in accordance with JIS B 0601 1994. The surface roughness RzJIS is a parameter also called "ten-point average roughness (Rzjis 94 in JIS B 0601 2013)", and the surface roughness is measured when the cutoff value λ is applied. C The value (unit: μm) of the sum of the average value of the peak height from the highest peak in descending order to the fifth peak and the average value of the valley depth from the deepest valley bottom in order of depth to the fifth valley bottom in the profile curve of the reference length obtained by the phase compensation high-pass filter. The lower limit of the surface roughness RzJIS is preferably 1.1 μm or more, and more preferably 1.3 μm or more. The upper limit of the surface roughness RzJIS is preferably 2.1 μm or less, and more preferably 1.9 μm or less.

[0026] Thus, by evaluating the surface of the rust-proof layer using the two parameters of non-contact roughness Spd and surface roughness RzJIS, the size of the vertical concavities and convexities on the surface of the rust-proof layer and the frequency on the plane can be known, and therefore, the bonding strength with the resin substrate can be estimated based on the anchoring effect on the resin substrate caused by such concavities and convexities of the rust-proof layer. Moreover, in the surface-treated copper foil of the present embodiment, by making the two parameters of non-contact roughness Spd and surface roughness RzJIS of the surface of the rust-proof layer within the prescribed range, the thickness of the rust-proof layer covering the roughened layer can also be estimated, thereby forming a rust-proof layer having a thickness that can fully withstand corrosive gases or particles.

[0027] The bonding strength of the surface-treated copper foil can be measured according to JIS C 6481. Specifically, a glass epoxy resin impregnated substrate equivalent to FR-5 is stacked on the surface of the anti-rust layer of the surface-treated copper foil as a copper-clad laminate, and the surface-treated copper foil is peeled off from the resin substrate of the copper-clad laminate under prescribed conditions in the vertical direction, and the minimum value of the load at this time (unit: kN / m) is taken as the bonding strength (peel strength). Preferably, the bonding strength of the surface-treated copper foil is maintained at 0.70 kN / m or more even after exposure to corrosive gas or particles, more preferably at 0.73 kN / m or more, and further preferably at 0.75 kN / m or more.

[0028] From the perspective of resistance to corrosive gases or particles, the material of the rust-proof layer is preferably nickel. In addition, the thickness of the nickel layer of the rust-proof layer is preferably 0.8 to 4.4 g / m2 in terms of the mass of nickel per unit area. 2 Although the non-contact roughness Spd and surface roughness RzJIS of the rust-proof layer vary depending on the non-contact roughness Spd and surface roughness RzJIS of the roughening layer covered with the rust-proof layer, the non-contact roughness Spd and surface roughness RzJIS of the rust-proof layer can be within the above range by making the thickness of the nickel layer of the rust-proof layer within the above range. The lower limit of the thickness of the nickel layer of the rust-proof layer is preferably 1.0 g / m2 in terms of the mass of nickel per unit area. 2 More preferably 1.5 g / m 2 In addition, the upper limit of the thickness of the nickel layer of the rust-proof layer is preferably 4.0 g / m 2 Below, more preferably 3.0g / m 2 above.

[0029] The thickness of the nickel layer of the rust-proof layer can be measured by atomic absorption spectrometry, high-frequency inductively coupled plasma (ICP: Inductively Coupled Plasma) emission spectrometry, fluorescent X-ray analysis, gravimetric measurement, or the like.

[0030] In addition, the rust-proof layer may be formed of a plurality of layers. For example, as the rust-proof layer, in addition to the nickel layer, a chromate-treated layer or a silane-coupled agent-treated layer may be further formed on the roughened layer side or the surface side of the nickel layer by chromate-treatment or silane-coupled agent treatment.

[0031] In order to maintain conductivity, the raw material of the rough layer is preferably copper, but in addition to copper, it may be tungsten, molybdenum, nickel, cobalt, iron, zinc, or a composite metal composed of two or more of them. The thickness of the rough layer is preferably 0.7 μm to 2.0 μm.

[0032] The thickness of the electrolytic copper foil is preferably 6 μm to 35 μm. If the thickness is too thin compared to 6 μm, it may be difficult to handle the electrolytic copper foil. On the other hand, if the thickness is too thick compared to 18 μm, when used for secondary batteries or printed wiring boards, the battery capacity may be reduced or it may be unfavorable to form a fine pattern due to the reduction in the number of windings. The lower limit of the thickness of the electrolytic copper foil is more preferably 6 μm or more, and more preferably 8 μm or more. The upper limit of the thickness of the electrolytic copper foil is more preferably 35 μm or less, and more preferably 18 μm or less.

[0033] Electrolytic copper foil generally has a shiny cathode surface which is the side in contact with the electrodeposition drum during its manufacturing process and a deposition surface formed by electroplating on the opposite side. The roughening layer and rust-proof layer may be formed on both the cathode surface and the deposition surface of the electrolytic copper foil, or may be formed on either surface. When formed on one surface, it is preferably formed on the deposition surface of the electrolytic copper foil.

[0034] The surface-treated copper foil of this embodiment may also have a composite metal layer between the electrolytic copper foil and the roughening layer as needed. The material of the composite metal layer is preferably a composite metal of copper and at least one metal selected from molybdenum, zinc, tungsten, nickel, cobalt and iron, and more preferably a composite metal of copper and at least one metal selected from tungsten and molybdenum and at least one metal selected from nickel, cobalt, iron and zinc. By providing such a composite metal layer between the electrolytic copper foil and the roughening layer, it has the advantage of being able to uniformly form a needle-shaped or granular copper plating layer on the surface of the copper foil.

[0035] [Method for producing surface-treated copper foil]

[0036] Hereinafter, an embodiment of the method for producing the surface-treated copper foil will be described. The method for producing the surface-treated copper foil of the present embodiment mainly includes a roughening treatment step and a rust-proofing treatment step.

[0037] The roughening treatment step is a step of forming a roughening layer by electroplating both sides or one side of the electrolytic copper foil. In this way, the surface of both sides or one side of the electrolytic copper foil can be roughened, for example, the non-contact roughness Spd of the roughening layer can be greater than 2.6 pieces / μm2 , making the surface roughness Rz of the roughened layer greater than 2.5μm. According to the rust-proofing layer formed later, the non-contact roughness Spd can be greater than 2.2 pieces / μm 2 , making the surface roughness Rz greater than 2.1μm, and the non-contact roughness Spd greater than 2.0 pieces / μm 2 , so that the surface roughness Rz is greater than 1.9 μm. In order to form such a roughened layer, it is preferred to use an acid copper electroplating bath. As specific electroplating bath composition and electroplating conditions, for example, the concentration of copper sulfate can be 130 g / L to 150 g / L, the concentration of sulfuric acid can be 80 g / L to 120 g / L, the bath temperature can be 25°C to 35°C, and the current density can be 1 A / dm 2 Up to 3A / dm 2 , and the treatment time is 10 seconds to 30 seconds. In addition, as a roughening treatment of the electrolytic copper foil, for example, a method using an acid copper electroplating bath disclosed in the Publication No. 53-39376 of Special Publication can be used, that is, a method in which a dendritic copper plating layer is formed by passing a current above the limiting current density through the acid copper electroplating bath, and then a coating electroplating is performed with a current lower than the limiting current density.

[0038] Although the above-mentioned electroplating bath composition and electroplating conditions are directed to the case of forming a roughened copper layer, even when a composite metal layer is formed on the surface of the electrolytic copper foil before the roughening treatment as described later, the roughening treatment can be performed by using the same acid copper electroplating bath as described above. In addition, in the roughening treatment step, it is preferred that the electrolytic copper foil be preliminarily washed with water or pickled with acid before electroplating.

[0039] The rust-proofing step is to electroplate the roughened layer formed on both sides or one side of the electrolytic copper foil to form a rust-proof layer on it. As a result, the roughened layer is covered by the rust-proof layer, and the non-contact roughness Spd of the rust-proof layer can be 1.4 pieces / μm. 2 Up to 2.6 / μm 2 , so that the surface roughness RzJIS of the rust-proof layer is 1.0 μm to 2.5 μm. In particular, it is preferred that the non-contact roughness Spd is 1.7 pieces / μm 2 Up to 2.0 / μm 2 The surface roughness RzJIS of the rust-proof layer is 1.3 μm to 1.9 μm. As the composition and plating conditions of the electroplating bath for forming such a rust-proof layer, for example, the concentration of nickel sulfate can be 300 g / L to 500 g / L, the concentration of boric acid can be 30 g / L to 50 g / L, the bath temperature can be 40°C to 60°C, and the current density can be 5 A / dm 2 Up to 15A / dm 2 The treatment time is 4 to 17 seconds. The thickness of the nickel antirust layer formed in this way can be 0.8 g / m2 in terms of the mass of nickel per unit area.2 Up to 4.4g / m 2 .

[0040] In addition, in the rust-proofing process, it is preferred to wash the surface of the roughened layer of the electrolytic copper foil with water before electroplating. In addition, in the rust-proofing process, as described above, in addition to the formation of the nickel layer, a chromate treatment or a silane coupling agent treatment may be combined as needed. The treatment conditions of the chromate treatment and the silane coupling agent treatment may be the known treatment conditions for the electrolytic copper foil.

[0041] The method for manufacturing the surface-treated copper foil of the present embodiment may further include, as needed, a step of forming a composite metal layer on the surface of the electrolytic copper foil on which the roughening layer is formed before the roughening treatment step. In order to form the composite metal layer, it is preferred to use an electroplating bath containing the metal ions of the materials of the composite metal layer. For example, as a specific electroplating bath composition and electroplating conditions for forming a composite metal layer of copper, molybdenum and zinc, for example, the concentration of copper sulfate may be 40 g / L to 60 g / L, the concentration of sodium molybdate may be 1 g / L to 3 g / L, the concentration of zinc sulfate may be 40 g / L to 60 g / L, the pH may be 2 to 3, the bath temperature may be 25°C to 35°C, and the current density may be 2 A / dm 2 Up to 8A / dm 2 , the treatment time is 2 seconds to 8 seconds. In addition, in order to form a roughened layer after forming a composite metal layer, for example, the method for producing a roughened copper foil disclosed in Japanese Patent No. 3949871 can be used, that is, a method of forming a composite metal layer using an electroplating bath containing ions of each metal of the composite metal layer with a current lower than the limiting current density of the bath, and then performing coating electroplating using an acid copper electroplating bath can be used.

[0042] In the step of forming the composite metal layer, it is preferred that the electrolytic copper foil be preliminarily washed with water or pickled with acid before electroplating.

[0043] Example

[0044] The present invention is described in more detail below by listing the examples and comparative examples of the present invention. However, the present invention is not limited to the following examples.

[0045] [Example 1]

[0046] (1) Manufacturing of surface treated copper foil

[0047] First, an electrolytic copper foil (manufactured by Nippon Electrolysis Co., Ltd., product number: SEED foil) with a thickness of 12 μm was pickled with 10% sulfuric acid for 20 seconds. Then, the copper foil was washed with water, and an electroplating solution composed of 50 g / L of copper sulfate pentahydrate, 2 g / L of sodium molybdate dihydrate, and 50 g / L of zinc sulfate heptahydrate was adjusted to pH 2.5 and a bath temperature of 30°C. The electroplating bath was used to carry out a 5A / dm 2 The two sides of the electrolytic copper foil are electroplated at a current density of 100 and a treatment time of 5 seconds to form a composite metal layer containing copper, molybdenum and zinc.

[0048] Next, the copper foil was washed with water and electroplated at 2 A / dm using an electroplating bath adjusted to 130 g / L of copper sulfate pentahydrate and 100 g / L of sulfuric acid at a bath temperature of 30°C. 2 Both sides of the copper foil were electroplated at a current density of 100 and a treatment time of 20 seconds to form a roughened layer composed of copper on the composite metal layer.

[0049] The copper foil was then washed with water and electroplated at 10 A / dm using a bath containing 400 g / L of nickel sulfate hexahydrate and 40 g / L of boric acid at a bath temperature of 50°C. 2 Both sides of the copper foil were electroplated at a current density of 100 and a treatment time of 4 seconds to form a rust-proof layer composed of nickel, thereby obtaining a surface-treated copper foil (Example 1).

[0050] (2) Characteristic test of surface treated copper foil

[0051] The amount of nickel per unit area of ​​the rust-proof layer of the surface-treated copper foil thus obtained was measured by a wavelength dispersive fluorescent X-ray spectrometer (ZSX Primus II manufactured by Rigaku Corporation) based on fluorescent X-ray analysis.

[0052] In addition, in order to measure the bonding strength of the surface treated copper foil, a glass epoxy resin impregnated substrate equivalent to FR-5 was stacked on one side of the surface treated copper foil as a copper clad laminate to prepare a test piece. According to JIS C 6481, the bonding strength between the surface treated copper foil and the resin substrate of the test piece was measured at room temperature (copper foil width: 1 mm). In addition, the bonding strength was measured in the state before treatment (normal state) and the state after treatment (after hydrochloric acid immersion) of the test piece immersed in a hydrochloric acid solution (concentration: 18%). In addition, the measurement of bonding strength was carried out by a tensile testing machine (TOYO SEIKI MANUFACTURER CO., LTD., STROGRAPH E3-L). The results are shown in Table 1.

[0053] Furthermore, the non-contact roughness Spd of the surface-treated copper foil was measured according to ISO 25178, and the surface roughness RzJIS of the surface-treated copper foil was measured according to JIS B0601 1994. It should be noted that the non-contact roughness Spd and the surface roughness RzJIS were measured using a laser microscope device (manufactured by KEYENCE Co., Ltd., VK-X150). The results are shown in Table 1.

[0054] [Example 2]

[0055] In the production of surface treated copper foil, in addition to using an electroplating bath adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 8 seconds to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0056] [Example 3]

[0057] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 12 seconds to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0058] [Example 4]

[0059] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 17 seconds to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0060] [Comparative Example 1]

[0061] In the production of the surface-treated copper foil, the surface-treated copper foil was produced in the same manner as in Example 1 except that the foil was immersed in an aqueous solution adjusted to 3.5 g / L of sodium dichromate dihydrate, pH 5.3, and a bath temperature of 28° C. for 10 seconds to form a rust-proof layer, and various property tests were performed. The results are shown in Table 1.

[0062] [Comparative Example 2]

[0063] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 1 second to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0064] [Comparative Example 3]

[0065] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 Except that the electroplating was performed at a current density of 1000 and a treatment time of 2 seconds to form a rust-proof layer composed of nickel, a surface-treated copper foil was produced in the same manner as in Example 1 and various property tests were performed. The results are shown in Table 1.

[0066] [Comparative Example 4]

[0067] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 20 seconds to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0068] [Comparative Example 5]

[0069] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, except that the electroplating was performed at a current density of 1000 and a treatment time of 40 seconds to form a rust-proof layer composed of nickel, and various property tests were performed. The results are shown in Table 1.

[0070] [Comparative Example 6]

[0071] In the production of surface treated copper foil, in addition to using a plating solution adjusted to 400 g / L nickel sulfate hexahydrate, 40 g / L boric acid, and a bath temperature of 50°C, the surface treated copper foil was plated at 10 A / dm 2 The surface treated copper foil was manufactured in the same manner as in Example 1, and various property tests were performed, except that the surface treated copper foil was electroplated at a current density of 1000 and a treatment time of 2 seconds to form a rust-proof layer composed of nickel, and then immersed in an aqueous solution adjusted to 3.5 g / L of sodium dichromate dihydrate, pH 5.3, and a bath temperature of 28°C for 10 seconds and the rust-proof layer was laminated. The results are shown in Table 1.

[0072] [Table 1]

[0073]

[0074] As shown in Table 1, the amount of nickel in the anti-rust layer is 0.8 g / m 2 Up to 4.4g / m 2 The non-contact roughness Spd of the surface of the anti-rust layer is 1.7 pieces / μm 2 Up to 2.0 / μm 2 The bonding strength between the surface treated copper foils of Examples 1 to 4 having a surface roughness RzJIS of 1.3 μm to 1.9 μm and the resin substrate was 0.70 kN / m or more both in the normal state and after hydrochloric acid immersion, and thus it was confirmed that excellent bonding strength could be maintained against corrosive gases.

[0075] On the other hand, in Comparative Example 1 in which the antirust layer is formed only by chromate treatment, although the bonding strength with the resin substrate under normal conditions shows a bonding strength similar to that of the example, after hydrochloric acid immersion, the bonding strength decreases to about 0.6 kN / m, confirming that it is greatly affected by corrosion. In addition, the amount of nickel in the antirust layer is less than 0.8, and the non-contact roughness Spd of the surface of the antirust layer is greater than 2.0 pieces / μm 2 Although the surface treated copper foils of Comparative Examples 2 and 3 with a surface roughness RzJIS greater than 1.9 μm showed a bonding strength with the resin substrate similar to that of the embodiment under normal conditions, the bonding strength decreased by more than 0.1 kN / m after immersion in hydrochloric acid, confirming that they were greatly affected by corrosion.

[0076] The nickel content of the anti-rust layer exceeds 4.4 g and the non-contact roughness Spd of the surface of the anti-rust layer is less than 1.7 pieces / μm 2 In the surface treated copper foils of Comparative Examples 4 and 5, whose surface roughness RzJIS is less than 1.3 μm, the bonding strength with the resin substrate is significantly low both in the normal state and after hydrochloric acid immersion, and sufficient bonding strength cannot be obtained. In addition, in Comparative Example 6, in which the rust-proof layer is formed by two layers of a nickel layer and a chromate treatment layer, the non-contact roughness Spd of the surface of the rust-proof layer is 1.7 pieces / μm. 2 Up to 2.0 / μm 2 The surface roughness RzJIS is 1.3μm to 1.9μm, but because the amount of nickel is less than 0.8, although the bonding strength with the resin substrate under normal conditions shows a bonding strength similar to that of the embodiment, after immersion in hydrochloric acid, the bonding strength decreases to about 0.6kN / m, confirming that it is greatly affected by corrosion.

Claims

1. A surface-treated copper foil comprising an electrolytic copper foil, a roughened layer covering at least one side of the electrolytic copper foil, and an anti-rust layer further covering the roughened layer, The antirust layer is at least one surface of the surface-treated copper foil, and the antirust layer has at least a nickel layer, and the thickness of the nickel layer is 0.8 g / m2 in terms of the mass of nickel per unit area. 2 Up to 4.4g / m 2 , The non-contact roughness Spd of the anti-rust layer measured according to ISO 25178 is 1.4 pieces / μm 2 Up to 2.6 / μm 2 , and the surface roughness RzJIS of the rust-proof layer measured according to JIS B 0601 1994 is 1.0 μm to 2.5 μm.

2. The surface-treated copper foil according to claim 1, wherein The anti-rust layer further comprises a chromate treatment layer and / or a silane coupling agent treatment layer.

3. The surface-treated copper foil according to claim 1 or 2, wherein A composite metal layer of copper and at least one metal selected from molybdenum, zinc, tungsten, nickel, cobalt and iron is provided between the electrolytic copper foil and the roughened layer.

4. A method for manufacturing a surface-treated copper foil, comprising: A roughening treatment step of forming a roughened layer on at least one surface of the electrolytic copper foil, wherein the non-contact roughness Spd of the roughened layer measured according to ISO 25178 is greater than 2.6 pieces / μm 2 , and making the surface roughness RzJIS of the roughened layer measured according to JIS B0601 1994 greater than 2.5 μm; and The rust-proofing step comprises forming at least a nickel layer as a rust-proofing layer on the roughened layer, wherein the thickness of the nickel layer is 0.8 g / m2 in terms of the mass of nickel per unit area. 2 Up to 4.4g / m 2 , wherein the non-contact roughness Spd of the anti-rust layer measured according to ISO 25178 is 1.4 pieces / μm 2 Up to 2.6 / μm 2 , and the surface roughness RzJIS of the rust-proof layer measured in accordance with JIS B 0601 1994 is 1.0 μm to 2.5 μm.

5. The method for producing a surface-treated copper foil according to claim 4, wherein: The rust-proofing step may include chromate treatment and / or silane coupling agent treatment in addition to forming the nickel layer.

6. The method for producing a surface-treated copper foil according to claim 4 or 5, wherein: It also includes the following step: before the roughening treatment step, a composite metal layer is formed on the surface of the electrolytic copper foil forming the roughening layer by an electroplating bath containing copper and at least one metal selected from the group consisting of molybdenum, zinc, tungsten, nickel, cobalt and iron.

Citation Information

Patent Citations

  • Copper foil for printed wiring board and method for producing same

    CN102362559A

  • Surface treated copper foil and copper-clad laminate

    CN110088361A